Are low-yield explosive ordnance disposal methods viable? - Alford, Roland; Hazael, Rachael; Critchley, Richard (IMCSE, 2022)
In 2021 reports began to appear online regarding a new underwater UXO clearance tech that produced a “low-yield” result. It claimed that the technology used did not cause deflagration (burning) but resulted in the munitions breaking up and scattering, causing the explosives to dissipate. The system used was referred to by the brand name Hydra-Jet.[1] Review of available material shows that at Seagreen Offshore Wind Farm, currently being constructed 27km off the Scottish coast in the North Sea [2], three sea mines were attacked using the Hydra-Jet and all three interventions either caused a detonation or a partial detonation. It is unlikely that this technology is 100% reliability and appears to show no improvement over proven low-order techniques such as shaped charges that use low-density reactive liners.[3] It is thought likely that the disruptive effect is produced by overpressure from the charge, placed at close range to the target causing high pressures that are designed to result in physical break-up of the munition rather than any more complex mechanism. The pressure readings taken of the events show that they strongly indicate that at least some of the explosives detonated. The published pressure measurements, indicating that there had been at least partial detonations, were reported to have presented a risk of harm to wildlife (harbour porpoise within approximately 4km) despite the results not having breached the operator’s licence thresholds.[4,5] The latest data from trials conducted by the national Physical Laboratories and Loughborough University might offer guidance for more stringent but achievable thresholds for future work.[6]